Economic Investigation of a Public Transport Support Policy: A Case Study at Budapest - Zefreh, Mohammad Maghrour; Meszaros, Ferenc; Junevičius, Raimundas; Torok, Adam (Promet - Traffic&Transportation, 2017)
This paper analyses the effect of supporting the public transport policy based on intersection controlling with the aim of tram priority in Budapest, as a case study. The hypothesis related to this study was that the support of public transport is only viable when the marginal benefit of public transport is higher than the marginal cost of individual transport. Therefore, the real costs of this support for the society were estimated. This study revealed that by applying this policy, the waiting time at intersections and CO2 emission-related costs have increased by about 13.7% and 14.2%, respectively. Besides, the estimated monetary gain of tram users would be 17,800 euro on a daily level total by applying the mentioned policy.